Instrument for assessing the quality of mobile emergency pre-hospital care: content validation - Rodrigo Assis Neves Dantas; Gilson de Vasconcelos Torres; Marina de Góes Salvetti; Daniele Vieira Dantas; Ana Elza Oliveira de Mendonça (SciELO, 2015)
OBJECTIVES To validate an instrument to assess quality of mobile emergency pre-hospital care. METHOD A methodological study where 20 professionals gave their opinions on the items of the proposed instrument. The analysis was performed using Kappa test (K) and Content Validity Index (CVI), considering K> 0.80 and CVI ≥ 0.80. RESULTS Three items were excluded from the instrument: Professional Compensation; Job Satisfaction and Services Performed. Items that obtained adequate K and CVI indexes and remained in the instrument were: ambulance conservation status; physical structure; comfort in the ambulance; availability of material resources; user/staff safety; continuous learning; safety demonstrated by the team; access; welcoming; humanization; response time; costumer privacy; guidelines on care; relationship between professionals and costumers; opportunity for costumers to make complaints and multiprofessional conjunction/actuation. CONCLUSION The instrument to assess quality of care has been validated and may contribute to the evaluation of pre-hospital care in mobile emergency services.